Speech and swallowing rehabilitation of post-partial mandibulectomy: a case report - Ravi, Sunil Kumar; Samyuktha, Vachavai Sai; Sumanth, Paramesh; Thupakula, Saraswathi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Squamous cell carcinomas of the oral cavity require multiple treatment approaches such as chemotherapy, radiotherapy, and surgical treatment. Glossectomy and mandibulectomy are the most common surgical treatment procedures for oral carcinoma with pre-, and post-surgical chemo-radiotherapy depending on the stage of cancer. The patients with glossectomy and mandibulectomy are at risk of developing a wide range of impairments in speech and swallowing functions due to surgical procedures and post chemo-radiation therapy (trismus and xerostomia). The present case report describes a 52-year-old male who had a history of oral squamous cell carcinoma and underwent wide excision of maxillar and mandibular regions who presented with severe speech and swallowing impairments. On examination of speech and swallowing functions, the patient exhibited oral dysphagia of moderate severity and poor speech intelligibility. The patient had undergone 50 speech and swallow therapy sessions over two months duration and post-therapy evaluation showed improvements in speech and swallowing functions. The patient had exhibited improvements in quality of life on various physical and functional domains post-rehabilitation. However, the improvements were limited due to the presence of trismus and hypernasality due to maxillar resection. This case report describes the importance of speech and swallowing rehabilitation to improve the post-surgical impairments in speech and swallowing functions and also the overall quality of life of patients with oral cancers.